Shaking Table Study on the Seismic Performance of Geogrid Reinforced Soil Retaining Walls - Xiaoguang Cai; Sihan Li; Honglu Xu; Liping Jing; Xin Huang; Chen Zhu (Advances in Civil Engineering)
This study presents experimental results from shaking table tests on a reduced-scale geogrid reinforced soil retaining wall (RSRW) to investigate the seismic response of the fundamental frequency, acceleration amplification, face displacement, backfill surface settlement, and reinforcement strain under different peak accelerations and durations. The fundamental frequency is in good agreement with the predicted values. The root mean square (RMS) acceleration amplification factors increase nonlinearly with the wall height and decrease with increasing seismic load, which is not regarded as a constant value. The distributions of the peak displacement are consistent with those of the residual displacement. The combination of the sliding and rotation is observed as the predominant mode of displacement, and the rotation mode is dominant. The positions near the face (35 cm) and the ends of the reinforcement (140 cm) demonstrated larger settlement than that of the central position (70 cm and 105 cm). The reinforcement strain increased with increasing peak acceleration and maximum values measured at the central layers. The trends of the potential failure surface are similar to those of the 0.3H bilinear failure surface. The friction coefficient is nonlinearly distributed along with the reinforcements, and the maximum friction coefficient appears at the top layer (F11).